Vulnerabilidade dos países exportadores de petróleo à própria riqueza: o caso dos países-membros da OPEP - Silva, Filipe de Pádua Fernandes (2018)
Oil-exporting countries may be vulnerable to their own wealth. These countries are subject to the resource curse hypothesis, which hinders their long-term socioeconomic development. This can derive from transmission mechanisms such as revenue volatility and political and institutional failures. Oil-exporting countries are also being challenged by environmental, market trends and technological breakthroughs, including shale revolution, climate change policies, and low-carbon technologies. These vulnerabilities cast doubt on the extent to which oil resources could serve in the future as sources of income and socio-economic development for oil-exporting countries. In order to measure these vulnerabilities, this study develops and applies a methodology based on indicators and multi-criteria analysis, the Analytic Hierarchy Process (AHP). The indicators are used for a static and comparative analysis of the vulnerability between oilexporting countries, being organized according to five criteria: Production, Market, Environment, Economic and Sociopolitical. Finally, the proposed methodology is applied to OPEC member countries in order to assess to what extent they are subject to the vulnerabilities. The results indicate that the United Arab Emirates, Qatar, Iran and Saudi Arabia are the least exposed countries, although fragile in certain aspects, while Iraq, Libya, Gabon, Nigeria and Angola are more susceptible to the risks and threats associated with the global oil market vulnerabilities.